Isolation, Characterisation of Four Gram Negative Environmental Bacteria and Bacteriophage Plaques Formation on Their Lawns: Life Sciences-Microbiology for health care - Maina, Alice Nyambura; Mwaura, Francis B; Jumba, Miriam; Kieft3, Kristopher (International Journal of Life Science and Pharma Research, 2021)
In the recent past a diversity of microorganisms has been isolated from various environmental waters of different regions in Kenya. Owing to the frequent spread of waterborne diseases in different regions where the communities do not have access to clean potable water the objective of this study was to isolate disease causing bacteria especially diarrhoea. In this study we isolated and characterised four species of Gram-negative bacteria from environmental waters used for domestic purposes by some communities in Kenya. Attempts were also made to isolate potential bacteriophages from the environmental waters for application as biocontrol agents in water decontamination. Clear, circular plaques of different sizes were formed on lawns of each of the bacterial species which could form the basis for bacteriophage isolation. The sources of water included Lake Victoria, rivers, wells, ponds, beaches, boreholes, springs and Indian Ocean. The four bacterial species characterized by 16S rRNA partial gene sequences and phylogenetic tree were: Vibrio cholerae, Escherichia coli: O83, Providencia sneebia and Proteus mirabilis. The 16S ribosomal RNA gene, partial sequences were deposited in GenBank under accession numbers: MN467398.1 and MN907473.1 (Escherichia coli), MN467401.1 (Providencia sneebia), MN467400.1 (Proteus mirabilis), MN467399.1, MN907465.1 and MN907464.1 (Vibrio cholerae) bacterial isolates. On the phylogenetic tree, P. sneebia grouped most closely to Morganella species, a closely related genus. Overall, the phylogenetic analysis also indicates the bacterial species isolated were not identical to bacteria in the database, but rather new isolates of the given species. The presence of these bacteria in the environmental waters of Kenya was an indication that the water was not safe for human consumption. Development of clear phage plaques was an indication of the presence of lytic phages that can be used for subsequent bacteriophage isolation from each bacterial strain after concentration.